2016
DOI: 10.1111/imj.13202
|View full text |Cite
|
Sign up to set email alerts
|

Benefit from cytoreductive nephrectomy and the prognostic role of neutrophil‐to‐lymphocyte ratio in patients with metastatic renal cell carcinoma

Abstract: Background: The role of cytoreductive nephrectomy (CN) for metastatic renal cell car-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Two ongoing clinical trials were identified (NCT00930033 and NCT01099423); however, not enough data were yet available for analysis. Finally, seven studies were included in the qualitative analysis (eight publications) [ 14 15 16 17 18 19 20 21 ]; five of them [ 14 15 16 18 21 ] reported the HR for overall survival of CRN versus no intervention ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two ongoing clinical trials were identified (NCT00930033 and NCT01099423); however, not enough data were yet available for analysis. Finally, seven studies were included in the qualitative analysis (eight publications) [ 14 15 16 17 18 19 20 21 ]; five of them [ 14 15 16 18 21 ] reported the HR for overall survival of CRN versus no intervention ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22,507 patients were included, with a median of 3,215 patients per study. Seven studies (eight publications) reported overall survival and one study reported toxicities related to tyrosine kinase inhibitors [ 14 15 16 17 18 19 20 21 ]. You et al [ 15 16 ] reported two publications but of the same study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this randomized trial, several retrospective observational studies have investigated whether CN provides a survival advantage in patients receiving targeted therapy [6][7][8][9][10][11][12][13][14][15][16][17][18]. These observational studies are limited to a varying degree by heterogeneous patient populations, selection bias, confounding and as a result, the strength of their evidence and related conclusions regarding the benefits of CN are limited.…”
Section: Cuaj -Consensus Statementmentioning
confidence: 99%
“…These observational studies are limited to a varying degree by heterogeneous patient populations, selection bias, confounding and as a result, the strength of their evidence and related conclusions regarding the benefits of CN are limited. Despite these limitations, nearly all available observational studies have identified a significant survival advantage in favor of CN for patients treated with targeted therapies [6][7][8][9][10][11][12][13][14][15][16][17][18]. For example, in a well performed analysis from the International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) (one of only two studies including Canadian patients), a 40% reduction in all-cause mortality was noted among patients receiving CN after controlling for known biases and adjustment for confounders [13].…”
Section: Cuaj -Consensus Statementmentioning
confidence: 99%